KOMUNITAS MEMBACA SEBAGAI PILAR PENDIDIKAN DI MASYARAKAT BADUY DESA KANEKES KECAMATAN LEUWIDAMAR KABUPATEN LEBAK-BANTEN - Helnafri Ankesa; Daden Fikruzzaman (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
The Baduy tribe is located in Kanekes Village on Mount Kendeng, where part of its territory is forest. This area is included in Banten Province, precisely in Lebak Regency, Leuidamar District. The Sundanese Indigenous people group consists of the Baduy Luar and Baduy Dalam Tribes. The Baduy Luar community is one that is experiencing quite rapid social change because basically this area has customary rules that are quite loose compared to the Baduy Dalam. Rumah Baca is a form of social change that has been formed in the Baduy Luar community. Rumah Baca is a reading community movement founded by Mulyono and Sarpin as a pillar of education for Baduy children in Kanekes Village, Lebak District, Banten. However, during the process of forming the reading community, there were still obstacles and challenges, both from within and outside the Baduy custom. The results of research conducted directly in the Baduy using the participation Action Research (PAR) method and SWOT analysis indicate that there are dominant factors as strengths and opportunities and inhibiting factors as weaknesses and challenges for the fluency of the reading community